Discontinuous Galerkin Methods for Solving a Frictional Contact Problem with Normal Compliance. (10th September 2018) - Xiao, Wenqiang; Wang, Fei; Han, Weimin
Abstract: Several discontinuous Galerkin (DG) methods are introduced for solving a frictional contact problem with normal compliance, which is modeled as a quasi-variational inequality. Consistency, boundedness, and stability are established for the DG methods. Two numerical examples are presented to illustrate the performance of the DG methods.